(untitled) (Ameghiniana, 2013)
BARREMIAN DECAPOD CRUSTACEANS FROM THE Tucu Tucu REGION, SANTA CRUZ PROVINCE. - Three macruran species, Palaeastacus terraeregina e (Etherídge), Enoploclytia sp. and Hoploparia longimana (Sowerby ) and one anomuran Protocallianassa patagonica n. sp. are described and illustrated from the Río Mayer Formation, Austral Basin, Patagonia. Based on the associated ammonite fauna, the material is assigned to the Late Barremian, Although the genera are cosmopolitan, they are not of chronostratigraphic value, the macruran species, as well as the anomuran, are important environmental indicators. Hoploporia longimana (Sowerby), Enoploclytia sp. and Protocallianassa patagonica n. sp. are mentioned and described for the first time in Argentina.